MR IMAGING FEATURES OF PRIMARY SCLEROSING CHOLANGITIS: A COMPREHENSIVE OVERVIEW OF IMAGE-BASED SCORING SYSTEMS FOR ASSESSMENT OF DISEASE SEVERITY AND PROGNOSIS - Kovač, Jelena; Janković, Aleksandra; Mitrović-Jovanović, Milica; Bogdanović, Aleksandar; Dugalić, Vladimir; Milovanović, Tamara (Medical Research, 2024)
Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver diseases marked by inflammation, fibrosis, and narrowing of the bile ducts, leading to cholestasis. Magnetic resonance cholangiopancreatography (MRCP) is the gold standard for the diagnosis of PSC allowing insight into biliary duct changes. The typical presentation of PSC includes multifocal anular and short-segmental strictures alternating with normal or slightly dilatated biliary ducts. Besides cholangiographic findings, magnetic resonance (MR) allows the assessment of liver parenchymal changes which might indicate the severity of the disease. The scoring systems based on MR findings, such as the ANALI score, and new computer-based software analysis termed MRCP+, provide a prediction of the course of disease and identify high-risk patients. Thus, MR with MRCP is a promising diagnostic tool for the integrative evaluation of PSC patients allowing not only initial diagnosis and detection of complications but also has prognostic significance.